KEEFEKTIFAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE CIRC (COOPERATIVE INEGRATED READING AND COMPOSITION) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMPN 31 PADANG - Nelisa, Mutiara; Mukhni, Mukhni; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
Background of this research is the low of solution of the teachersâ effort to solve the studentsâ problem in learning mathematic at eight grade in SMPN 31 Padang. The purposes of this research: 1) to know how the improvement of the students at ability to solve the studentsâ problem in learning mathematic at eight grade in SMPN 31 Padang using cooperative learning model type CIRC. 2) to know what is the achievement the studentsâ to save the studentsâ problem in learning mathematic at eight grade in SMPN 31 Padang by using cooperative learning model type CIRC better than using conventional learning. The type of this research is experimental research. The result of the hypothesis testing is P-value 0,000 lower than Î± 0,05, so the hypothesis of the result is accepted. It can be concluded that the studentsâ ability to solve the studentsâ problem in learning mathematic by using cooperative learning model type CIRC better than conventional learning at eight grade in SMPN 31 Padang. Â